Development of Arabic Reading Skills Test Items Based on Common European Framework of Reference for Languages Theory - Safira Aina Najiyah; Ihwan Mahmudi; Muhammad Ismail; Latif Fatus Sa’diyah (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2026)
Introduction: The lack of standarized assessment instruments aligned with the CEFR remains a significant challenge in evaluating student’s Arabic reading proficiency within the Indonesian educational context. In particular, there is a critical need for instruments that bridge local curricula with the Common European Framework of Reference for Languages (CEFR). Research Objectives: This study aims to develop valid and reliable Arabic reading skills test items based on the CEFR proficiency descriptors. Methodology: To address this gap, this research employed a Research and Development approach using the 4D model, which consists of define, design, develop, and disseminate stages. However, the implementation of this study was limited to the first three stages: defining needs, designing the test blueprint, and developing test items.  The participants of this study were 259 fifth-grade students of Pondok Modern Darussalam Gontor Putri 1, selected using the Slovin formula. The initial blueprint comprised 119 test items distributed across six CEFR proficiency levels, ranging from A1 to C2. The test items were constructed in various formats, including multiple-choice, true-false, and matching questions. To ensure the quality of the instrument, expert validation and limited field trials were conducted. The data obtained were analyzed to determine content validity, empirical validity, reliability, item difficulty level, and discrimination power. Results: The results revealed that 72 items met the validity criteria and were suitable for use. The reliability analysis showed a coefficient of 0.99, indicating a very high level of reliability. Most of the valid items were categorized as easy, although several items required revision to improve their discrimination power and better differentiate between high- and low-performing students. Unique Contribution: This study contributes practically by providing Arabic language teachers in Indonesia with a standardized, CEFR-based assessment tool that can support accurate measurement of student’s reading competencies and enhance the effectiveness of Arabic reading instruction. Conclusion: Overall, the findings demonstrate thet the developed instrument is valid, reliable, and appropiate for assessing student’s reading profiency based on CEFR standards. Recommendations: Further research is recommended to implement the disseminate stage and expand the use of this instrument in broader contexts.